2021
DOI: 10.1007/s10943-021-01408-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Religious Activities on Quality of Life and Cognitive Function Among Elderly

Abstract: Religiosity and spirituality have previously been found to have significant effects on mental and physical health. This study aimed to compare elderly people utilizing different types of religious activities in their daily routine and the effects upon their quality of life and cognitive function. A cross-sectional study was conducted among elderly people dwelling in suburban areas of Malaysia. The Malay version of Short Form (36) Health Survey (SF-36), Geriatric Depression Scale (GDS-15), Older Americans Resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
4
11
0
3
Order By: Relevance
“…MCI is a cognitive disorder that lies on a continuum between normal aging and dementia 39 , and has a high prevalence in the older adults 40,41 . Our ndings support earlier studies reporting that cognitive impairment was associated with increased mortality, lower MMSE scores in particular increased risk of all-cause mortality 42 . A meta-analysis that pooled the data from nine high quality studies found that MCI assessed by MMSE is an independent risk factor of mortality among older adults in China 43 .…”
Section: Discussionsupporting
confidence: 92%
“…MCI is a cognitive disorder that lies on a continuum between normal aging and dementia 39 , and has a high prevalence in the older adults 40,41 . Our ndings support earlier studies reporting that cognitive impairment was associated with increased mortality, lower MMSE scores in particular increased risk of all-cause mortality 42 . A meta-analysis that pooled the data from nine high quality studies found that MCI assessed by MMSE is an independent risk factor of mortality among older adults in China 43 .…”
Section: Discussionsupporting
confidence: 92%
“…QoL needs to be approached holistically and it has been proven that religious activities have a positive impact on health and well-being, especially on QoL. 18 Another Brazilian study showed an association between religion and all domains of the adapted Ferrans & Powers Q uality of Life Index, as in the present study. 14 Our study found a significant association between the number of people living in the same household and mental health.…”
Section: Discussionsupporting
confidence: 70%
“…Religiosity and spirituality have previously been found to have significant effects on mental and physical health. QoL needs to be approached holistically and it has been proven that religious activities have a positive impact on health and well‐being, especially on QoL 18 . Another Brazilian study showed an association between religion and all domains of the adapted Ferrans & Powers Quality of Life Index, as in the present study 14 …”
Section: Discussionsupporting
confidence: 67%
“…Transcripts indicated that the significance and usefulness of this need were supported by statements from residents. Performing prayers was shown to have a positive influence on elderly people's everyday life and encouraged a feeling of being safe, calm, peaceful, and more confident (32,33). In elderly people's life, attending to their spiritual needs ensures that they have an opportunity to find meaning for the end of their life and draw themselves closer to God.…”
Section: Discussionmentioning
confidence: 99%